The Impacts of Recolonisation of an Urbanised River by Native and Non-native Species - Rotherham, Ian D. (Frontiers in Ecology and Evolution, 2021)
The roles of native and non-native species in the recolonisation of the River Don in South Yorkshire, England, are considered through the lens of environmental history. Notable as one of the most polluted river systems in Western Europe, the Don-Dearne-Rother catchment runs west to east from South Yorkshire and North Derbyshire and drains a significance part of middle England. However, from their origins in the foothills of the high Pennine hills with peat-bogs and heather moorland, the constituent rivers run through upland-fringe farmland and then into the major urban and industrial centres of the region. By the mid-twentieth century the reaches of these watercourses were grossly polluted and physically degraded too. However, from the 1970s onwards there began a slow recovery in environmental quality and this has continued to the present day. This paper focuses on the ecological changes in the main urban zones of the River Don catchment and includes the constituent rivers namely the Sheaf, the Porter, the Rother, the Dearne, the Rivelin, and the Loxley. Importantly, though conservationists may be reluctant to accept it, the new ecology which has emerged throughout the catchment is irreparably changed from that of the seventeenth and eighteenth centuries. That landscape itself was already majorly altered from the countryside described in the Domesday account of 1086, and that too was much changed from the Romano-British landscape of a millennium earlier. The landscape is changing and is permanently changed and so too is the ecology that it now supports. In this context, a hybrid or recombinant ecology has been observed to develop through the process of eco-fusion and is made up of an intimate mix of native and non-native species.